PRINCIPLE MEDIATION OF DOMESTIC VIOLENCE AS CRIMINAL ACT - Sandy Ari Wijaya (Fakultas Hukum Universitas Mataram, 2014)
Penal mediation is a process of extra judicial settlement for criminal case. The application ofpenal mediation on criminal law is to give the justice and protection to the victims of which it isnot accommodate by legality aspect in Indonesia criminal law. The existence of penal mediationprinciple with legal certainty affect the domestic violence (KDRT). The inconsistence continueswhen the penal mediation process relevance is applied to serious domestic violence that violate thehuman rights. The legality principle and human rights must be aligned with the penal mediationprinciple associated with domestic violence (KDRT) to reach ideal justice in the substance ofvictim protection in the domestic violence law, and in general the alignment of the new substancein Indonesian Criminal Code (KUHP) to protect the values and spirit of Indonesian country.Key word: penal mediation principle, legality, domestic violence ( KDRT), HumanRights